Experimental and numerical simulation of pull-out response in textile-reinforced concrete - Venigalla, S.G.; Nabilah, A.B.; Mohd Nasir, N.A.; Safiee, N.A.; Abd Aziz, F.N.A. (Elsevier, 2023)
Textile-reinforced concrete (TRC) is a construction material that uses continuous fibres such as carbon to create a lightweight and durable structural system. Even though TRC possesses vast possibilities in terms of its usage, identification of bond-slip behaviour at the material interface is one of the limitations that need to be addressed. Based on the literature, there are difficulties in determining the bond-slip relationship both experimentally and numerically, creating inconsistency in the results. This study aims to determine the bond-slip relation of TRC through pullout tests and validated through finite element analysis to replicate the actual bond-slip behaviour at the interface. The bond characteristics of TRC were assessed using a double-sided pullout test setup with different bond lengths of textile, namely 20 mm, 30 mm, 40 mm, 50 mm, and 60 mm. It was noticed that in short bond specimens (20 mm, 30 mm, and 40 mm), the phenomena of pullout failure were due to weakened bond at the interface until pre-peak, followed by complete loss of adhesive bond due to debonding of fibre. However, for the specimens with longer bond lengths (50 mm and 60 mm), rupture of the textile leading to a sudden loss of bond capacity was observed. Additionally, the general fibre pullout phenomenon curve was used to explain the debonding process. Using a calibrated tri-linear bond-slip interface relation, the numerical model was developed to simulate the pull-out response of fibre. The numerical model was able to reproduce experimental results, including maximum load, post-peak behaviour, and interfacial slip. The difference of maximum shear stress between pull-out tests and numerical modelling was within 2 % while the slip difference was between 4 and 31 % for different bond lengths. However, for longer bond lengths, the fibre failure mode was due to pullout instead of rupture, unlike the experimental results.